Education to Give in Processes Information and Communication Technologies (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In our country education in the system school sciences in education from ICT efficient use current is an issue. Exactly information technologies universal tool of education and not only in students knowledge, skill and qualifications formation enable gives, perhaps personal features to develop, to know interests satisfies.